Evaluation of concrete flaw detection capability by means of ultrasonic tests - Lorenzi, Alexandre; Argenta Chies, Josue; Santos Adamatti, Deise; Pinto da Silva Filho, Luiz Carlos (Revista ALCONPAT, 2017)
Ultrasonic Pulse Velocity (UPV) tests are being increasingly used to detect flaws in concrete. This work is part of a large experimental program aimed at studying the influence of key technological variables on detection capacity using UPV in real size elements. For this investigation two large concrete elements were cast, with some objects introduced in one to simulate possible concrete flaws due to inadequate casting. Furthermore, to check the capacity of detecting unseen voids with UPV tests, gradual perforations with different depths were made from the unmonitored face. The results confirm that UPV analysis is a very good tool to detect concrete faults, up to some depth.